Refolding and purification of recombinant L-asparaginase from inclusion bodies of E. coli into active tetrameric protein - Upadhyay, Arun K.; Singh, Anupam; Mukherjee, K. J.; Panda, Amulya K. (Frontiers in Microbiology, 2014)
A tetrameric protein of therapeutic importance, Escherichia coli L-Asparaginase-II was expressed in Escherichia coli as inclusion bodies. Asparaginase inclusion bodies were solubilized using low concentration of urea and refolded into active tetrameric protein using pulsatile dilution method. Refolded asparaginase was purified in two steps using ion-exchange and gel filtration chromatographic techniques. The recovery of bioactive asparaginase from inclusion bodies was around 50 %. The melting temperature (Tm) of the purified asparaginase was found to be 64 °C. The specific activity of refolded, purified asparaginase was found to be comparable to the commercial asparaginase (190 U/mg). Enzymatic activity of the refolded asparaginase was high even at four molar urea solutions, where the inclusion body aggregates are completely solubilized. From the comparison of chemical denaturation data and activity at different concentrations of guanidine hydrochloride, it was observed that dissociation of monomeric units precedes the complete loss of helical secondary structures. Protection of the existing native-like protein structure during solubilization of inclusion body aggregates with 4 M urea improved the propensity of monomer units to form oligomeric structure. This helped in improved recovery of asparaginase in bioactive tetrameric form.